2019
DOI: 10.2196/13163
|View full text |Cite
|
Sign up to set email alerts
|

Therapist-Guided Tablet-Based Telerehabilitation for Patients With Aphasia: Proof-of-Concept and Usability Study

Abstract: Background Aphasia is the loss or impairment of language functions and affects everyday social life. The disorder leads to the inability to understand and be understood in both written and verbal communication and affects the linguistic modalities of auditory comprehension, verbal expression, reading, and writing. Due to heterogeneity of the impairment, therapy must be adapted individually and dynamically to patient needs. An important factor for successful aphasia therapy is dose and intensity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…A very recent study (Bersano and Pantoni, 2020) also confirmed this need for acute stroke patients who, due to COVID-19, suffered from a shortage of services and delays in time-dependent treatments and diagnostic work-up. In order to circumscribe the consequences of the COVID-19 pandemic, one possible strategy might be to set up tele-rehabilitation and home-based services, which have been already successfully implemented for aphasia rehabilitation (Zhou et al, 2018;Gerber et al, 2019;Chang and Boudier-Revéret, 2020) and to focus on specific rehabilitation programs which allow the patients, who are no longer followedup in therapy, to keep training their communication skills, and avoiding further deterioration. This would not add excessive costs to the healthcare system since it could be easily supported by the patients' families.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study (Bersano and Pantoni, 2020) also confirmed this need for acute stroke patients who, due to COVID-19, suffered from a shortage of services and delays in time-dependent treatments and diagnostic work-up. In order to circumscribe the consequences of the COVID-19 pandemic, one possible strategy might be to set up tele-rehabilitation and home-based services, which have been already successfully implemented for aphasia rehabilitation (Zhou et al, 2018;Gerber et al, 2019;Chang and Boudier-Revéret, 2020) and to focus on specific rehabilitation programs which allow the patients, who are no longer followedup in therapy, to keep training their communication skills, and avoiding further deterioration. This would not add excessive costs to the healthcare system since it could be easily supported by the patients' families.…”
Section: Discussionmentioning
confidence: 99%
“…In a usability study, it was shown that the app is well accepted by patients and therapists. 28 Patients are provided with an overview of exercise collections assigned by a speech and language therapist. Collections are intended to train a specific language impairment (eg, semantically categorising items).…”
Section: Interventionmentioning
confidence: 99%
“…The exercise types cover all levels of language organisation, that is, phonology, grammar (consisting of morphology and syntax) and semantics. 28 Exercises consist of fixed (eg, written language, placeholders), supportive (eg, videos, audio tracks, images) and response elements (eg, unarranged letters), except exercises of the type word repetition which exclusively provide videos as fixed elements. Unmovable and required elements to solve the exercise are referred to as fixed elements.…”
Section: Exercisesmentioning
confidence: 99%
See 2 more Smart Citations